Design, Synthesis, and Application in OFET of a Quinoxaline-Based D-A Conjugated Polymer - Dai, Zhicheng; Zhang, Daohai; Zhang, Haichang (Frontiers in Chemistry, 2022)
A novel alternating donor-acceptor polymer PQ1 is designed and synthesized by palladium-catalyzed Stille coupling between quinoxaline as electron-deficient unit and indacenodithiophene (IDT) as electron-rich groups. The polymer PQ1 present not only a strong intramolecular charge transfer (ICT) effect, which is benefit for the charge transport within the single molecules, but also a narrow electrochemical band gap and a high HOMO energy level. In addition, the optical absorption study indicates that the PQ1 film exhibit a good aggregation, which is advantage for the charge transport between the neighboring molecules. As a consequent, the PQ1 present a p-type semiconductor properties with a high hole mobility up to 0.12 cm2 V−1 s−1.This study suggested the great potential of quinoxaline-type chromophores in constructing novel organic semiconductors.